IMPLEMENTASI MANAJEMEN RISIKO TERINTEGRASI SESUAI ISO 31000 DI RUMAH SAKIT UMUM PUSAT DOKTER KARIADI SEMARANG - Dharma Wahyu Edhy; Fitri Lukiastuti (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
Enterprise risk management (ERM) plays a very important role in overseeing business processes to achieve goals and prevent risks that may arise. This study aims to determine the implementation of MRT in dr. kariadi hospital semarang, with the output of the organization's risk register. The method used is qualitative and refers to ISO 31000 and Regulation of the Minister of Health No. 25 of 2019 concerning the implementation of integrated risk management in the organizational unit of the Ministry of Health. Data were obtained through in-depth interviews with 11 sections/fields and 19 installations at the Kariadi Hospital Semarang to obtain a hospital risk map. The result of the research is the compilation of the hospital risk register, namely the Assessment and its mitigation plan. By compiling a list of hospital risks, it will help decision makers / team ranks in carrying out missions and overseeing hospital processes in order to achieve good hospital organizational governance.